The Activity and Safety of Anlotinib for Patients with Extremity Desmoid Fibromatosis: A Retrospective Study in a Single Institution - Zheng C; Zhou Y; Wang Y; Luo Y; Tu C; Min L (Dove Medical Press, 2020)
Chuanxi Zheng,* Yong Zhou,* Yitian Wang, Yi Luo, Chongqi Tu, Li Min Department of Orthopedics, West China Hospital, Sichuan University, Chengdu, Sichuan 610041, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li MinDepartment of Orthopedics, West China Hospital, Sichuan University, No. 37 Guoxuexiang, Chengdu 610041, People’s Republic of ChinaTel +86 13760311476Fax +86 028 85582944Email minli1204@scu.edu.cnPurpose: Desmoid fibromatosis (DF) is an aggressive fibroblastic neoplasm with a high propensity for local recurrence. Although multiple therapeutic modalities seem effective for DF, the standard systemic treatment for symptomatic and progressive DF remains controversial. As targeted therapy, tyrosine kinase inhibitors have been recently reported to contribute to the treatment of DF. Thus, the purpose of this study was to assess the efficacy and safety of anlotinib, a novel multi-kinase angiogenesis inhibitor, in patients with DF.Patients and Methods: We retrospectively collected the clinical medical records of patients with extremity DF who received anlotinib between January 2019 and January 2020 in our center. Anlotinib was started with a dose of 8 mg daily and adjusted according to the drug-related toxicity. Tumor response was assessed by the Response Evaluation Criteria in Solid Tumors 1.1 criteria. Progression-free survival (PFS) was identified as the primary endpoint and analyzed using the Kaplan–Meier method.Results: In total, 21 (6 male, 15 female) consecutive patients with DF were enrolled. The median medication time was nine months (Q1, Q3: 7.5, 10.5). None of the patients achieved a complete response, but eight (38.1%) patients achieved a partial response and ten patients (47.6%) achieved disease stability. Three (14%) patients developed progressive disease and the 3-, 6-, and 12-month PFS rates were 95.2%, 90.5%, and 84.0%, respectively. The disease control rate was 86.0% (18/21) and the objective response rate was 38.1% (8/21). Moreover, 15/21 (71.4%) patients achieved a reduction in tumor size, accompanied with a decrease in T2-weighted signal intensity on magnetic resonance imaging and clinical benefit.Conclusion: Anlotinib was effective against DF with an acceptable safety profile, and significantly slowed the disease progression. Further, multicenter studies with a longer follow-up time are needed to characterize fully the clinical application of anlotinib in DF.Keywords: desmoid fibromatosis, anlotinib, tyrosine kinase inhibitor, targeted therapy